ANALYSING FINANCIAL HEALTH AND PERFORMANCE: A COMPREHENSIVE RATIO ANALYSIS OF JAY AMBE TEA COMPANY, JALGAON - Prof. Prachi Jagwani; Ms. Lovely Mittal (International Engineering Journal For Research & Development, 2024)
This research aims to conduct a thorough ratio analysis of Jay Ambe Tea Company based in Jalgaon, investigating key financial ratios to assess the company's financial health and performance. The study will delve into liquidity, profitability, leverage, and efficiency ratios to provide valuable insights into the company's operational efficiency, financial stability, and overall economic viability. The findings from this research will contribute to a better understanding of Jay Ambe Tea Company's financial standing and inform stakeholders, investors, and management for strategic decision-making.